2006
DOI: 10.1016/j.jvs.2006.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting outcomes of open surgical repair of pararenal aortic aneurysms: A 10-year experience

Abstract: PAAA repair can be performed with low mortality. Renal insufficiency is the most frequent complication, but avoiding renal artery bypass, prolonged mesenteric ischemia time, or left renal vein transection may improve results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
134
3
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(153 citation statements)
references
References 26 publications
9
134
3
7
Order By: Relevance
“…Some other studies have reported low rates of patients requiring hemodialysis during the postoperative period; 18,25 while others report that up to 10% of patients with prior renal dysfunction subjected to surgery on the juxtarenal aorta required hemodialysis afterwards. 26 West Jr et al 1 reported that 4.1% of patients with CAIO temporarily required hemodialysis during the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies have reported low rates of patients requiring hemodialysis during the postoperative period; 18,25 while others report that up to 10% of patients with prior renal dysfunction subjected to surgery on the juxtarenal aorta required hemodialysis afterwards. 26 West Jr et al 1 reported that 4.1% of patients with CAIO temporarily required hemodialysis during the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, these technical difficulties pose an increased risk of mortality and morbidity for patients with a history of laparotomy; comorbidities such as coronary artery disease; renal insufficiency; history of steroid use; and chronic obstructive pulmonary disease. 11,12) Recent reports of the open repair of JAA have revealed that the perioperative mortality ranges from 2.5 % to 6.3 %. [12][13][14] The endovascular approach is expected to be beneficial to treat JAA in the high risk patients.…”
Section: Follow-upmentioning
confidence: 99%
“…4 Approximately 8-20% of AAAs are pararenal, which includes both juxtarenal and suprarenal AAAs. Juxtarenal AAAs are infrarenal aneurysms that involve the lower margin of the origin of the renal arteries.…”
Section: Definitionmentioning
confidence: 99%